“GENDER-RELATED FEATURES OF FUNCTIONAL RECOVERY AFTER LEFT AND RIGHT HEMISPHERE STROKES: CLINICAL AND REHABILITATION ANALYSIS” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the gender-related features of functional recovery processes following strokes in the left and right cerebral hemispheres from clinical and rehabilitation perspectives. The study analyzes the dynamics of recovery, severity of neurological symptoms, and differences in rehabilitation effectiveness between male and female patients after stroke. The importance of an individualized approach in clinical and rehabilitation practice is highlighted, and recommendations for developing rehabilitation programs that consider gender factors are provided. The article serves as a scientific and practical foundation aimed at improving recovery outcomes and enhancing health restoration measures after stroke.